Prognostic role of serum thymidine kinase 1 activity in patients with hormone receptor–positive metastatic breast cancer: Analysis of the randomised phase III Evaluation of Faslodex versus Exemestane Clinical Trial (EFECT). (June 2019) - McCartney, Amelia; Biagioni, Chiara; Schiavon, Gaia; Bergqvist, Mattias; Mattsson, Karin; Migliaccio, Ilenia; Benelli, Matteo; Romagnoli, Dario; Bonechi, Martina; Boccalini, Giulia; Pestrin, Marta; Galardi, Francesca; et al.
Abstract: Background: Thymidine kinase 1 (TK1) plays a critical role in DNA synthesis and cell proliferation. Recent studies have shown potential for serum TK1 activity (sTKa) as a prognostic marker and indicator of early response to endocrine therapy in advanced breast cancer. The aim of this study is to assess the correlation between sTKa and patient outcome. Patients and methods: The Evaluation of Faslodex versus Exemestane Clinical Trial (EFECT) was a double-blind, double-dummy, randomised trial of fulvestrant versus exemestane after progression on non-steroidal aromatase inhibitor therapy, in postmenopausal women with advanced breast cancer. Retrospective analyses of serum archived from EFECT were conducted. sTKa was assessed using the DiviTum® assay on samples collected at baseline, after three and six months of endocrine therapy,  and at disease progression. Results: The median time to progression (mTTP) for patients with low baseline sTKa levels was 5.03 months (95% confidence interval [CI]: 3.91–5.89) versus 2.57 months (95% CI: 2.04–3.52) in patients with high sTKa baseline levels (P < 0.0001). On treatment, patients whose sTKa increased from baseline had a significantly shorter mTTP (3.39 months, 95% CI: 2.14–4.11) than those without an sTKa increase (5.39 months, 95% CI: 4.01–6.68) (P = 0.0045). Similar results were observed in the separate EFECT treatment arms. After adjusting for major prognostic factors, sTKa remained an independent marker. Conclusion: sTKa is a potential circulating prognostic marker in patients with advanced breast cancer treated with endocrine therapy. It may also represent a tool for upfront identification of endocrine therapy resistance and early positive response to therapy. Independent validation of these results is warranted. Highlights: Retrospective analyses of sera from the Evaluation of Faslodex versus Exemestane Clinical Trial to assess the association between serum thymidine kinase 1 activity (sTKa) and outcome. Low baseline sTKa correlated with longer median time to progression (mTTP). Stable or decreased sTKa while on endocrine treatment correlated with longer mTTP. After adjusting for prognostic factors, sTKa remained an independent marker. sTKa may identify early endocrine resistance and monitor response in sensitive disease.